EFFECT OF THICKNESS OF OVERLAYING CLAY LAYER OF LOWLAND REGION ON SENSITIVITY OF LATERAL DEFLECTION OF LONG PILES EMBEDDED IN NONHOMOGENEOUS SOIL – PART IIB: NUMERICAL STUDY OF CLAY AND PILE PARAMETERS - D. H. Hafez; B. B. Budkowska (Lowland Technology International, 2006)
This part of the paper is a direct continuation of part I and part IIA of the paper. The first part of the paper presented the theoretical formulation of the sensitivity of the lateral head deflection of piles embedded in nonhomogeneous soil consisting of clay overlying sand to changes in the design parameters. Parts IIA and IIB cover the numerical sensitivity studies based on this theoretical formulation. Part IIA studied the effect of variation in sand parameters on the variation of the lateral pile-head deflection. This part (part IIB) presents the sensitivity of the lateral pile-head deflection to variations in the clay and pile parameters. The numerical sensitivity results are graphically plotted along the pile length. The effect of the thickness of the overlying clay layer on these sensitivity results is investigated. This effect of non-homogeneity of soil is of significant importance to areas in which the overlaying clay layer has variable thicknesses such as in lowland areas.